Modernity and the Face - Werth, Margaret (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
Around 1900, the face took on new forms, functions, and meanings. Modes of figuring identity and aesthetic value or registering individual and social experience through the face changed. Georg Simmel's studies of modernity and the privileged status of the face are tied to reconfigurations of the face in literature (Proust), art (Redon), and film (the close-up), highlighting the dislocation of oppositions between interiority/exteriority, proximity/distance and human/machine.